Análise de viabilidade técnica e financeira para implantação de uma usina solar fotovoltaica de minigeração distribuída com potência instalada de 1 MW - Orlandi, Luiza Ramos (2022)
The continuous increasing of renewable energy sources on the Brazilian energy grid gives solar energy more and more attention and emphasis due to its several environmental and economic benefits. Furthermore, Brazil has an advantage due to its great energetic potential due to the solar incidence on the country when compared to other leading nations in the generations of this kind of energy. Thus, this document will present a technical and economic analysis of a 1MW photovoltaic system conected on grid in Ivinhema, Mato Grosso do Sul. This study aims to show how financially attractive the investment in a great solar power plant can be aiming at joining the Eletric Energy Compensation System (EECS).